Pengaruh Pengetahuan, Motivasi, dan Promosi terhadap Keputusan Menjadi Nasabah Bank Syariah Indonesia Cabang Sungai Penuh dengan Minat sebagai Variabel Intervening - Alim Erdiansah; Denta Safitri; Usdeldi Usdeldi; Titin Agustin Nengsih (Ekonomis: Journal of Economics and Business, 2026)
This study aims to determine the effect of Knowledge, Motivation, and Promotion on the Decision to Become a Customer of Bank Syariah Indonesia Full River Branch with Interest as an Intervening Variable. This study uses a quantitative approach in which all data obtained is measured objectively and systematically. The population taken in this study were the people of Kerinci district and Sungai Penuh City. The sampling technique uses nonprobability sampling, namely couta sampling, the sample in this study is the community in the city of Sungai Penuh and Kerinci Regency. Where the river city has 8 sub-districts and 4 villages and kerinci district with 11 sub-districts. In Sungai Penuh City a couta will be taken which will be sampled as many as 86 respondents and in Kerinci Regency a sample of 124 respondents will be taken, so this study uses 200 people as respondents. Data collection methods using questionnaires and data analysis techniques using SEM-PLS analysis. Based on the research results show that: 1). knowledge and promotion have a positive effect on decisions while motivation has a negative effect on decisions; 2). promotion has a positive effect on interest while knowledge and motivation have a negative effect on interest; 3). knowledge, motivation, and promotion have a positive effect on decisions through interest as an intervening variable.